Effect of Hyperglikemic Conditions on Ovarian Structure and Estrous Cycle of Mice (Mus musculus L) - Eva Tyas Utami (Jurnal ILMU DASAR, 2009)
Streptozotocin cause hyperglycemic condition in mice. The objective of this study was to determine whether the hyperglycemic conditioned by streptozotocin (STZ) has an impact at folicullar atretic and estrous cycle prolonged. Mice were injected by STZ until hyperglycemic condition was reached. The vaginal smear was recorded daily for twice estrous cycle. Mice were sacrificed soon after the last vaginal smear observation. The ovary was removed, prepared by parafin method and stained by hematoxylin-eosin.The result showed that hyperglycemic causes increasing the number of atretic follicles, decreasing the number of corpus luteum and prolonged of estrous cycle.